NON-STEROIDAL ANTI-INFLAMMATORY DRUGS VS. PARACETAMOL: DRUG AVAILABILITY, PATIENTS' PREFERENCE AND KNOWLEDGE OF TOXICITY - Zamir, Quratulain; Nadeem, Amina (Journal of Ayub Medical College Abbottabad, 2016)
Background: Self-medication is a common practice which is influenced by level of education, society factors and health care facilities availability. In our region, Pakistan, it is very common and awareness regarding prescription implementation needs to be ensured. Hence the current study highlights the preference, availability and knowledge of toxicity of non-steroidal anti-inflammatory medications and paracetamol in Pakistan. Method: It was a Descriptive, cross sectional, conducted in Rawalpindi and Islamabad, Pakistan from May to august 2012. A total of 1000 questionnaires comprising of 21 questions were distributed to the persons with age groups from 18 years to 40 years. Non-probability convenience sampling technique was used for results deduction. Data was analysed using descriptive statistics. Results: The most commonly used medicine was Mefenamic acid (n=191, 40.8%). Paracetamol was second on the priority list (n=146, 31.3%). About 178 out of 467(38.1%) used these medications for headache. Very few responders knew about the toxic doses of the medicines they used. Only 52 (11%) were aware of the raised bleeding tendency being the most common side effect of acetylsalicylic acid and 129 (28%) were aware of liver damage by paracetamol toxicity. Conclusion: In Pakistan, common people take NSAIDs and Paracetamol without prescription and majority of them are unaware of the side effects of these medicines. This is the reason it is important to make the general public aware of the problems they may face if they misuse or over use the drugs without the prescription. Keywords: Aspirin; paracetamol; Non-steroidal Anti-inflammatory Drugs; Paracetamol; Drug availability; Patients' Preference; Knowledge; Toxicity